Public Spending and Learning Outcomes of Basic Education at the District Level in Indonesia - Jasmina, Thia (UI Scholars Hub, 2016)
Since 2009, the Indonesian government has fully allocated 20 percent of its budget on education. Though the increase of financial resources has led to an improvement of the access to education, challenges on the quality of education persist. By employing a cross-districts analysis in Indonesia during 2010-2015, this study aims to analyze the impact of government spending on the adjusted-national examination scores at the junior secondary education. This study shows that the central and local government spending have no significant impact on the scores. Whereas, the central government spending on teachers, and the socioeconomic factors such as poverty and health are significant determinants.